Connectivity knowledge and the degree of structural formalization: A contribution to a contingency theory of organizational capability - Rogerio S. Victer (Journal of Organization Design, 2020)
The objective of this study is to develop a contingency theory of organizational capability based on the identification of decision variables relevant to the design of firms. The paper supports a model in which superior performance is the result of the proper fit between applied knowledge and organizational structure. More specifically, the study shows that the degree of structural formalization adopted by an organization reflects how knowledge controls the flow of action. The study identifies a functionally distinctive type of knowledge used to regulate the temporal order of tasks called connectivity knowledge. The influence of connectivity knowledge on the degree of organizational formalization is empirically tested on data collected in the healthcare sector. Applying a longitudinal logistic regression model on a dataset of 105 hospitals located in New York and New Jersey, this paper measures and compares the odds of key therapeutic tasks being provided by formalized hospital arrangements in which physicians work as employees instead of as autonomous professionals. Empirical results provide preliminary support to the core hypothesis correlating the volume of connectivity knowledge applied in therapeutic services to the degree of structural formalization adopted by a hospital.
Keywords: 650; Knowledge management; Capability theory of the firm; Contingency theory; Organizational design